Comparison of multidimensional frailty score, grip strength, and gait speed in older surgical patients. Issue 2 (8th January 2020) - Choi, Jung‐Yeon; Kim, Kwang‐il; Choi, YoungRok; Ahn, Sang‐Hoon; Kang, Eunyoung; Oh, Heung‐Kwon; Kim, Duck‐Woo; Kim, Eun‐Kyu; Yoon, Yoo‐Seok; Kang, Sung‐Bum; Kim, Hyung‐Ho; Han, Ho‐Seong; et al.
Abstract: Background: Frail older adults are at increased risk of post‐operative morbidity compared with robust counterparts. Simple methods testing frailty such as grip strength or gait speed have shown promising results for predicting post‐operative outcome, but there is a debate regarding the most appropriate and precise frailty assessment method. We compared the predictive value of multidimensional frailty score (MFS) with grip strength, gait speed, or conventional risk stratification tool for predicting post‐operative complications in older surgical patients. Methods: From January 2016 to June 2017, 648 older surgical patients (age ≥ 65 years) were included for analysis. MFS was calculated based on the preoperative comprehensive geriatric assessment. Grip strength and gait speed were measured before surgery. The primary outcome was a composite of post‐operative complications (e.g. pneumonia, urinary tract infection, delirium, acute pulmonary thromboembolism, and unplanned intensive care unit admission). The secondary outcome was the 6 month all‐cause mortality. Results: Among 648 patients (mean age 76.6 ± 5.4 years, 52.8% female), 66 (10.2%) patients experienced post‐operative complications, and the 6 month mortality was 3.9% ( n = 25). Grip strength, gait speed, MFS, and American Society of Anesthesiologists (ASA) classification could predict post‐operative complication but only MFS (hazard ratio = 1.581, 95% confidence interval 1.276–1.959, P < 0.001) could predict 6 month mortality after adjustment. MFS (C‐index = 0.750) had a superior prognostic utility compared with age (0.638, P = 0.008), grip strength (0.566, P < 0.001), and ASA classification (0.649, P = 0.004). MFS improved the predictive value on age [C‐index of 0.638 (age) vs. 0.758 (age + MFS), P < 0.001] and ASA classification [C‐index of 0.649 (ASA) vs. 0.765 (ASA + MFS), P < 0.001] for post‐operative complication; however, gait speed or grip strength did not provide additional prognostic value in both age and ASA. Conclusions: Multidimensional frailty score based on preoperative comprehensive geriatric assessment showed better utility than age, grip strength, gait speed, or ASA classification for predicting post‐operative complication and 6 month mortality. MFS also showed incremental predictive ability for post‐operative complications with the addition of age and ASA classification. Accordingly, MFS is superior to grip strength or gait speed for predicting complications among older surgical patients.